Two Buddhas seated side by side : a guide to the Lotus Sūtra - Lopez, Donald S., Jr., 1952-; Stone, Jacqueline Ilyse (Princeton University Press, 2019)
"The Lotus Sutra is one of the most influential works in the vast literature of Buddhism. Here, in exploring its many meanings, two scholars consider how this work was understood by its compilers in India and, centuries later, by Nichiren, its famous proponent in Japan"--